PENGARUH PENEMPATAN KERJA, PELATIHAN DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SAWIT ASAHAN INDAH KABUPATEN ROKAN HULU - Mirza Yusfa Munawir; Dewita Suryati Ningsih; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Sawit Asahan Indah Rokan Hulu District. The purpose of this study was to determine the effect job placement, traning and non-physical environment on employee job satisfacition. The study population was 80 employees and is set with models census. Research variables used are the job placement, traning and non-physical work environment as independent variables and job satisfacition dependent variable. Methods of data analysis using multiple linear regression analysis aided by SPSS version 21. Research shows that the work placement and a significant positive effect Satisfaction Good work means more work placement can then job satisfaction will be improved, in particular in PT. Sawit Asahan Indah. Training variables influence positively and significantly Against Job satisfaction. Searching Google Articles Thus, more Effective Employee Training Conducted Indeed in basically able to increase job satisfaction, particularly in Sawit Asahan Indah. Non Physical Environment Variables work and significant positive effect on job Satisfaction, particularly in PT Sawit Asahan Indah. Increasingly High non Physical work environment employees in the Company, then the work will satisfaction can be improved. Research shows that variable work placement, training and non-physical work environment, Operate Together Against significant influence job satisfaction. If the Third Aspect can be improved simultaneously Operating Then Job satisfaction in PT Sawit Asahan Indah will be able to be increased significantly Operate.Keywords: Job Placement, Traning, Non-physical Work Environment, Job Satisfacition